Estudo geofísico sobre a erosão fluvial do Rio Guamá na orla da Universidade Federal do Pará, Belém (PA) - DIAS, Gustavo Nogueira (Universidade Federal do Pará, 2014)
The present work is a geophysical study of a riverbank exposed to erosion and it aims to evaluate its use for detecting areas degraded by critical erosion stage before they collapse. The studied area is situated 600m alongside Guamá River – between Tucunduba River Bridge and Canoeing Pier at Federal University of Pará. The area has different kinds of erosion contentions along its way such as cement walls and cement bags. Therefore the place is considered a laboratory to test geophysics expertise in detecting areas affected by imperceptible process so that it can act before they erode. The following four geophysical methods were used: spontaneous potential –SP; electroresistivity; Slingram – LIN and ground penetration radar – GPR. The measures were taken during both low and high tides in order to map the preferable subsuperficial paths the water runs through. In general, tides increase oscillations in SP measures, electroresistivity and LIN as well as increase the reflections intensity from GPR compared to low tide measures and during high tide, measures show compared to low tide: I) In erosion affected area there is a voltage decrease in SP, a resistivity decrease in electroresistivity, a conductive increase in LIN as well as an intensity increase of the reflections and a continuity disturbance in GPR. II) In contained areas there is an increase of the SP voltage, an increase of the resistivity from electroresistivity, a decrease of the LIN conductivity and an ease in the reflections from the GPR and a reduction of tides global effects. Despite the difficulties, the results show Geophysics can be a useful tool not only on preventing affected areas from collapsing but also on analyzing the effectiveness of previous contention woks.